Risk premium shocks, monetary policy and exchange rate pass-through in the Czech Republic, Hungary and Poland - Balázs Vonnák (Magyar Nemzeti Bank, 2010)
This paper investigates the role of monetary policy in a small open economy, where exchange rate shocks are important. VAR models are estimated for the Czech Republic, Hungary and Poland. Contemporaneous and sign restrictions are imposed in order to identify the effect of monetary policy and risk premium shocks. Estimates from the same model for Canada, Sweden and the UK are used as benchmark for developed economies with low inflation. The results suggest that the typical size a of risk premium shock renders it almost impossible for the interest rate policy to smooth the exchange rate with the aim of minimising inflationary consequences. On the other hand, low inflation may decrease the exchange rate pass-through, which helps the monetary policy ignore exchange rate shocks.
Keywords: E31; E52; F31; 330; monetary policy; risk premium shocks; exchange rate pass-through; structural VAR; sign restriction; Geldpolitik; Risikoprämie; Schock; Exchange Rate Pass-Through; VAR-Modell; Tschechische Republik; Ungarn; Polen; Kanada; Schweden; Großbritannien